Non-Steroidal Anti-Inflammatory Drugs used as a Treatment Modality in Subarachnoid Hemorrhage - M.H. Young, Adam; K.Karri, Surya; S. Ogilvy, Christopher (Current Drug Safety, 2012)
Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most frequently prescribed therapies worldwide. Meta-analysis data indicate the potential for myocardial infarction, cerebrovascular incident, heart failure, renal failure and arterial hypertension. Here we review the mechanisms of their actions and the potential for therapeutic use in subarachnoid hemorrhage. Searches were performed using PubMed with the search terms “subarachnoid hemorrhage”, “NSAID”, “treatment”, “management”, “cerebral aneurysm”, and “vasospasm” from 1970 to February, 2012. Articles were also identified through searches of the Cochrane library and searches of the authors' own files. Only papers published in English were reviewed.There are considerably mixed views on the potential impact of NSAIDs on the treatment and prevention of SAH. Whilst theoretically, the potential for positive intervention in the condition is huge, little effect appears to be measurable in clinical practice.
Keywords: SAH